Sarcoptic mange in wombats—A review and future research directions. Issue 2 (18th November 2017) - Old, J. M.; Sengupta, C.; Narayan, E.; Wolfenden, J.
Summary: Sarcoptic mange is caused by the mite Sarcoptes scabiei and has recently been recognized as an emerging infectious disease of wildlife worldwide. The mite is one of the main causes of population decline in southern hairy‐nosed ( Lasiorhinus latifrons ) and bare‐nosed wombats ( Vombatus ursinus ). This review focuses on Sarcoptes scabiei infestations in wombats and provides insights into why the disease may be so prevalent in wombats. Current treatment practices and trials conducted in the field to reduce the incidence of sarcoptic mange in wombats are described and critically reviewed. Current and potential future avenues of research are discussed.